2015
DOI: 10.13031/trans.58.11119
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the Physicochemical and Biological Characteristics of Foaming Swine Manure

Abstract: Foam accumulation in deep-pit manure storages is an increasing concern for swine producers because of the logistical and safety-related problems it creates. To investigate this phenomenon, samples of swine manure were collected over a 13-month period from 58 swine production facilities in Iowa with varying levels of foam accumulation. Samples were tested for a number of physical, chemical, and biological parameters including pH, total and volatile solids, volatile fatty acid concentration, long-chain free fatt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…In general, the BMP magnitudes reported in our study were substantially higher than the magnitudes reported for samples collected from deep-pit production swine barns. Van Weelden et al (2015) reported an average value of 121 ±86 mL CH 4 g -1 VS for both foaming and non-foaming samples, with foaming samples showing a slightly lower average value; in our study, BMP values of 155 to 395 mL CH 4 g -1 VS were found. The current BMP results were comparable to other studies, which showed that fresh swine manure ranged between 244 to 480 mL CH 4 g -1 VS (Burton and Turner, 2003;Møller et al, 2004;King et al, 2011) depending on ration.…”
Section: Methane Productionsupporting
confidence: 44%
See 1 more Smart Citation
“…In general, the BMP magnitudes reported in our study were substantially higher than the magnitudes reported for samples collected from deep-pit production swine barns. Van Weelden et al (2015) reported an average value of 121 ±86 mL CH 4 g -1 VS for both foaming and non-foaming samples, with foaming samples showing a slightly lower average value; in our study, BMP values of 155 to 395 mL CH 4 g -1 VS were found. The current BMP results were comparable to other studies, which showed that fresh swine manure ranged between 244 to 480 mL CH 4 g -1 VS (Burton and Turner, 2003;Møller et al, 2004;King et al, 2011) depending on ration.…”
Section: Methane Productionsupporting
confidence: 44%
“…The foaming capacity and stability were tested according to the method described by Van Weelden et al (2015). In brief, air was passed through a 300 mL manure sample at 0.2 L min -1 until a constant foam height was recorded.…”
Section: Foaming Capacity and Stabilitymentioning
confidence: 99%
“…Data were collected to describe each farm's feed ingredients. Manure sampling procedures and characterization (e.g., total solids, methane production rate) have previously been described [7]. Additional manure characterization (i.e., pH, moisture, organic N) was performed by Midwest Laboratories (Omaha, NE).…”
Section: Experimental Designmentioning
confidence: 99%
“…Pair-ended bacterial 16S rRNA gene sequences were assembled using the Ribosomal Database Project (RDP) Paired-end Reads Assembler 7 with minimal overlap of 80 bases (-o 80) and minimal assembled length 350 bases (-l 350). Assembled sequences with an expected maximum error-adjusted Q score less than 25 over the entire sequence were eliminated.…”
Section: Dna Sequence Processingmentioning
confidence: 99%